The Influence of Entrepreneurial Orientation on the MSME Performance with Business Model Innovation as a Mediating Variable (Study on MSME in Driyorejo District Gresik Regency) - Kanza Amira Ramadhany; Eko Wahjudi (STKIP Taman Siswa Bima, 2025)
This research is motivated by the increasing growth of MSME, which has led to increasingly fierce competition. However, bussines performance remains suboptimal due to entrepreneurs' inability to identify business opportunities and poor adaptation to environmental changes. This study aims to analyze and explain the influence of entrepreneurial orientation on MSME performance with Business Model Innovation as a Mediating Variable. This type of research is quantitative with an explanatory approach. Data collection was carried out by distributing questionnaires to MSME owners in the culinary sector of Driyorejo District, Gresik Regency. Sampling was carried out using a purposive sampling method and resulted in 62 saturated samples. Data processing and analysis in this study was carried out using Structural Equation Model (SEM) analysis with WrapPLS software version 7. The results of this study indicate that entrepreneurial orientation has a positive and significant effect on MSME performance, entrepreneurial orientation has a positive and significant effect on business model innovation, business model innovation has a positive and significant effect on MSME performance, and entrepreneurial orientation has a positive and significant effect on MSME performance through business model innovation.